Development of a caffeic acid-phthalimide hybrid compound for NADPH oxidase inhibition - Santos, Willian Henrique dos [UNESP]; Yoguim, Maurício Ikeda [UNESP]; Daré, Regina Gomes; Da Silva-Filho, Luiz Carlos [UNESP]; Lautenschlager, Sueli Oliveira Silva; Ximenes, Valdecir Farias [UNESP] (Royal Society of Chemistry (RSC), 2021)
NADPH oxidases are pharmacological targets for the treatment of inflammation-based diseases. This work presents the synthesis and study of a caffeic acid/phthalimide hybrid compound (C2) as a potential inhibitor of NADPH oxidases. Throughout the study, we have compared compound C2 with its precursor caffeic acid (C1). The redox properties were compared using three different antioxidant methodologies and showed that C2 was slightly less effective than C1, a well-established and robust antioxidant. However, C2 was three-fold more effective than albumin (used as a model protein). This chemical feature was decisive for the higher efficiency of C2 as an inhibitor of the release of superoxide anions by stimulated neutrophils and enzymatic activity of cell-free NADPH oxidase. Docking simulation studies were performed using the crystal structure of the recombinant dehydrogenase domain of the isoform NOX5 of C. stagnale, which retains the FAD cofactor (PDB: 5O0X). Considering that C2 could bind at the FAD redox site of NOX5, studies were conducted by comparing the interactions and binding energies of C1 and C2. The binding energies were -50.30 (C1) and -74.88 (C2) (kJ mol-1), which is in agreement with the higher efficacy of the latter as an NADPH oxidase inhibitor. In conclusion, incorporating the phthalimide moiety into caffeic acid was decisive for its effectiveness as an NADPH oxidase inhibitor.